جريمة سب الصحابة رضي الله عنهم وعقوبتها في الفقه الإسلامي - بن الشلي, نور (جامعة الوادي University of Eloued, 2016)
هذا المقال كما هو ظاهر من عنوانه يعالج جريمة سب الصحابة رضي الله عنهم باستحضار الأدلة التي تجرمها، ويناقش أنواع العقوبة المقررة فقها لها باعتبارها نوعا من جرائم ازدراء الدين. ABSTRACT: This article, as is apparent from its title It addresses the crime of insulting the companions of the prophet God bless them by invoking Substances criminalizing This act and Discuss the types of punishment prescribed in this regard, as a sort of contempt of religion crimes.
The Crime Of Insulting The Companions Of The Prophet, God Bless Them And Its Punishment The Islamic Jurisprudence
Keywords: الصحابة، الجريمة، العقوبة، السُنّة، السبّ، الدِّين; Companions- crime –Punishment- tradition-Insults- Religion